2018
DOI: 10.1111/clr.13390
|View full text |Cite
|
Sign up to set email alerts
|

Original vs. non‐original abutments for screw‐retained single implant crowns: An in vitro evaluation of internal fit, mechanical behaviour and screw loosening

Abstract: Objectives To assess the internal accuracy, mechanical behaviour under static load and screw loosening before and after cyclic loading of implant‐supported crowns restored with original components or with two compatible non‐original brands. Materials and Methods Sixty‐three dental implants were divided into three groups (n = 21 each): Group 1 used original components, and groups 2 and 3 used non‐original components. Internal accuracy was measured throughout a cross section of the sample groups (n = 8) using sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 30 publications
3
36
0
Order By: Relevance
“…In the case of nonoriginal abutments the tendency of stress to concentrate at the abutment screw increased the risk for microfracture, and therefore for microgap formation. This was con rmed by the results of a previous investigation [8,34] where original abutments after in vitro fatigue testing showed the best accuracy within their components as well as the lowest values of screw loosening.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In the case of nonoriginal abutments the tendency of stress to concentrate at the abutment screw increased the risk for microfracture, and therefore for microgap formation. This was con rmed by the results of a previous investigation [8,34] where original abutments after in vitro fatigue testing showed the best accuracy within their components as well as the lowest values of screw loosening.…”
Section: Discussionsupporting
confidence: 61%
“…For the internal accuracy test, a sample size of 4 was required for a power of 80% and an alpha value of 0.05 [34]. Statistical analysis was executed using SPSS® software (version 21.0, SPSS Inc., Chicago, IL, USA).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the torque loss of the original abutments was significantly lower than that of the copy abutments. In another in vitro study, Alonso‐Pérez et al came to a similar conclusion, verifying that the internal fit of the connection was crucial to the mechanical behavior of the assembly, and so that the original components excelled.…”
Section: The Factors Contributed To Abutment Screw Looseningmentioning
confidence: 99%
“…Although implant‐supported prostheses have demonstrated long‐term success rates, a large number of mechanical complications have been reported . Many studies have shown that the loosening and fatigue fracture of the abutment or prostheses screw are the most common failure modes for screw‐retained prostheses, especially in single implant‐supported restorations in the premolar and molar regions . Moreover, veneer chipping was the main problem observed on all‐ceramic dental crowns and fixed partial dentures .…”
Section: Mechanical Concernsmentioning
confidence: 99%
“…[42][43][44][45][46][47][48] Many studies have shown that the loosening and fatigue fracture of the abutment or prostheses screw are the most common failure modes for screw-retained prostheses, especially in single implant-supported restorations in the premolar and molar regions. [49][50][51][52] Moreover, veneer chipping was the main problem observed on all-ceramic dental crowns and fixed partial dentures. 53 These mechanical problems are mostly related to the materials and the design of the prosthetic components.…”
Section: Mechanical Concernsmentioning
confidence: 99%